Major Contributors to Hospital Mortality in Very-Low-Birth-Weight Infants: Data of the Birth Year 2010 Cohort of the German Neonatal Network - Stichtenoth, G.; Demmert, M.; Bohnhorst, B.; Stein, A.; Ehlers, S.; Heitmann, F.; Rieger-Fackeldey, E.; Olbertz, D.; Roll, C.; Emeis, M.; Mögel, M.; Schiffmann, H.; Wieg, C.; Wintgens, J.; Herting, E.; Göpel, W.; Härtel, C. (Klinische Pädiatrie, 2012)
The German Neonatal Network (GNN) is a prospective cohort study with the focus on long term development of very-low-birth-weight infants. It was the aim of this study to determine detailed information on causes of mortality in the GNN birth cohort 2010.Major contributors to hospital mortality were recorded by the attending neonatologists for the cohort of very-low-birth-weight (VLBW) infants born in centres of the German Neonatal Network (GNN) in 2010. The data quality was approved by on-site monitoring.2 221 VLBW infants were born in GNN centres in 2010, and death occurred in 221 infants. Male infants carried a higher risk than females (58.8% males among non-survivors vs. 51.7% among survivors, p=0.047). In 11 infants, the major contributor to death was not determined by the attending neonatologist. In 25 infants born at the limit of viability, comfort palliative care was primarily initiated and 14 infants had lethal malformations. The majority of non-survivors suffered from inflammatory diseases including sepsis- or necrotizing enterocolitis (NEC)-associated death (n=56). Respiratory pathology was a major contributor to death in 65 infants including 11 infants who died from pulmonary haemorrhage.Potentially preventable complications of preterm birth such as sepsis, NEC and pulmonary haemorrhage predominate the major contributors to mortality in the GNN 2010 cohort. In order to decrease the rate of these associated deaths, future trials should focus on prophylaxis and therapy optimization strategies for these outcomes.
Keywords: mortality; very low birth weight infants; sepsis; respiratory distress syndrome